Human health risk assessment on the consumption of fruits and vegetables containing residual pesticides: A cancer and non-cancer risk/benefit perspective. (November 2017) - Valcke, Mathieu; Bourgault, Marie-Hélène; Rochette, Louis; Normandin, Louise; Samuel, Onil; Belleville, Denis; Blanchet, Carole; Phaneuf, Denise
Abstract: Pesticide residues in food is a public health concern. This study aimed to evaluate health risk and benefit associated with chronic consumption of fruits and vegetables (F&V) containing residual pesticides in the province of Quebec, Canada. Based on a representative sample of Quebecers ( n  = 4727, aged 1–79) enrolled in the Canadian nutrition survey, population's mean chronic dietary exposure through consumption of F&V was evaluated for 169 different pesticide active ingredients (PAI), including 135 for which toxicological reference values (TRV) were available in the literature. Total lifetime cancer risk was estimated to be 3.3 × 10 − 4 considering the 28 substances for which an oral slope factor was also available. Non-cancer risk quotients greater than 1 were obtained at the 95th percentile of children's exposure for 10 of the 135 PAIs, and considering the most severe pesticide-specific TRV. Dithiocarbamates and imazalil are the authorized PAI that contribute the most to cancer and non cancer risk; they are therefore identified as "priority" PAI. For each estimated case of cancer triggered by PAI exposure, at least 88 cases were deemed prevented by the consumed F&V, based on the population's etiological fraction of the cancer risk that F&V prevent. Concluding, chronic health risks investigated are low and health benefits of F&V consumption by far outweigh the PAI-related risk. However, risk estimates are not negligeable and uncertainties remain. Thus, reducing PAI exposure through F&V consumption with a particular focus on "priority" PAI mentionned above, while maintaining an abundant and varied F&V diet, is desirable. Graphical abstract: Highlights: Exposure to pesticide in fruits & vegetables (F&V) was assessed for 4727 Quebecers. Cancer and non-cancer risk were assessed while accounting for uncertainties. The protective effect of F&V against cancer and other diseases was accounted for. Estimated cancer risk is not negligible and non-cancer risk is low. The benefits of F&V consumption strongly outweigh the risk of pesticide residues.